Evaluation Of Morphological Diversity Of Lupinus angustifolius L. Depending On Growth Stages - Vlasova, Elena (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Based on the results of long-term description of VIR collection of Lupinus angustifolius L. it was found that the intensity of phenotypic expression of the some morphological features depends on the growth stage of plant. Meanwhile, the intraspecific classification is based on a visual assessment of morphological signs. The corolla coloring and the painting on the seed testa characterize the species. The color of cotyledon and vegetative organs and the presence or absence of anthocyanin on the keel petal are the diagnostic signs of the subspecies. In addition to the diagnostic characters of the classification, there are also a number of features of intraspecific diversity, some of which are very useful in crop breeding. These are the type of branching, the color of endocarp and the width of leaf. In this regard the available numeral system of lupin growth stages was complemented with data of the estimated morphological traits of Lupinus angustifolius by growth stages. These data are presented in a tabular format. Also, data on the regularity of manifestation of the features during the growing season are presented in that Table. The presented Table would contribute to the unification of monitoring of the morphological descriptions at a time of subjective visual perception. It can also help newcomers to correctly assess the intraspecific diversity of Lupinus angustifolius.